PERBANDINGAN EFEKTIVITAS TEH HIJAU DAN TEH HITAM DALAM MENURUNKAN KADAR TRIGLISERIDA PADA HEWAN COBA MODEL HIPERLIPIDEMIA - Monica Regina Ngantung; Rita Dewi; Jojor Lamsihar Manalu (Atma Jaya Catholic University of Indonesia, 2020)
Introduction: Hyperlipidemia is the cause of 18% of cardiovascular disease and 56% of ischemic heart disease worldwide. According to the World Health Organization (WHO), in 2017, cardiovascular disease is the leading cause of death worldwide. In its role against cardiovascular disease, green tea and black tea can be used as an alternative treatment in reducing triglyceride levels.Methods: This study is an in vivo experimental. This experiment using 16 Rattus norvegicus rats strain Sprague-Dawley induced with lard and raw quail egg yolk before and divided into two groups; green tea and black tea groups. Treatment is carried out for 17 days and checking the triglyceride level before and after intervention using test strip and tools from Lipid Pro. Data were collected and analyzed using the Shapiro-Wilk test, paired t-test, and unpaired t-test. Results: The results showed that the data were normally distributed (Shapiro-Wilk test p> 0.05). Treatment with green tea and black tea for 17 days led to a significant drop in triglyceride level (paired t-test p <0.05), and there is a significant difference between the effectiveness of the intervention group (unpaired t-test p <0.05).Conclusion: There was a significant decrease in rats’ triglyceride levels in the administration of green tea and black tea, and green tea is more effective than black tea in reducing triglyceride levels on hyperlipidemic Rattus Norvegicus.